Pengaruh Green Human Resource Management Terhadap Inovasi Ramah Lingkungan dalam Sistem Pelaporan Keberlanjutan, Dimediasi oleh Komitmen Organisasi - Nduru, Julian; Sumiati, Sumiati (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2025)
This study aims to examine the effect of organizational commitment mediating This study aims to examine the influence of Green Human Resource Management on Environmentally Friendly Innovation Behavior in the Mediation of Organizational Commitment at the Padang City Regional Financial and Asset Management Agency. The type of research used is quantitative research. The population of the study was all employees of the Padang City Regional Financial and Asset Management Agency taken as respondents totaling 63 people, with sampling using the total sampling method where the entire population will be used as a sample. The data sources used are secondary and primary data. Data analysis techniques usingsmartPLS software(Partial Least Square) 4.0.Based on the results of the study, it shows that the Green Human Resource Management variable has a positive and significant effect on Environmentally Friendly Innovation Behavior. The Green Human Resource Management variable has a positive and significant effect on Organizational Commitment. The Green Human Resource Management variable has a positive and significant effect on Organizational Commitment.Organizational Commitment has a positive and significant effect on Environmentally Friendly Innovation Behavior. The Green Human Resource Management variable has a positive and significant effect on Environmentally Friendly Innovation Behavior in the mediation of Organizational Commitment